PERENCANAAN DALAM MANAJEMEN EVENT ORGANIZER - Agus Purnomo; Amin Warjo; Meity Suryandari (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
ABSTRACT This study examines planning practices within Event Organizer (EO) management in Indonesia as the pivotal entry point of the four-stage cycle (planning, organizing, execution, monitoring–evaluation). Adopting a qualitative descriptive exploratory multi-case design, data were collected via semi-structured interviews, build show strike observations, and document reviews (briefs, rundowns, stage/site plans, budgets, risk registers, post-event reports). Data were analyzed using the Miles Huberman Saldaña interactive model. Findings indicate that higher-maturity EOs align event briefs with clients’ strategic objectives, standardize planning artefacts (proposals, macro rundowns, site/stage plans, initial risk logs), and enforce buffer times, load-in windows, and change-control gates. During execution, disciplined tech rehearsals and show calling reduce downtime and improve issue/incident closure rates. CHSE compliance is most visible in hygiene health safety components, while sustainability practices (waste reduction, segregation) are emerging yet not fully systematized under SNI ISO 20121. Digital tools (cloud task boards, shared calendars, real-time checklists) and the integration of content planning with experience design enhance sponsor deliverable fulfillment and audience satisfaction. The study proposes a performance “triad” process governance, risk & safety, and experience design as the foundation for strengthening EO planning quality, and recommends measurable sustainability targets embedded from the planning stage. Keywords: Event Planning; Event Organizer; Event Management; Risk Management; CHSE (MICE); ISO 20121; Experience Design